Site-specific control of multiple mineralizations using a designed peptide and DNA. Issue 39 (23rd August 2016) - Usui, Kenji; Ozaki, Makoto; Yamada, Aoi; Hamada, Yoshio; Tsuruoka, Takaaki; Imai, Takahito; Tomizaki, Kin-ya
Abstract : We have developed a site-specific precipitation method of multiple inorganic compounds using DNA and a designed peptide containing a peptide nucleic acid sequence and an inorganic compound-precipitating sequence. This system represents a powerful tool in nanotechnology. Abstract : We have developed a site-specific method for precipitating multiple inorganic compounds using target DNA and a designed peptide consisting of a peptide nucleic acid (PNA) sequence and an inorganic compound-precipitating sequence. This system for controlled site-specific precipitation represents a powerful tool for use in nanobiotechnology and materials science.